Molecular epidemiology and genetic diversity of Anaplasma and Theileria spp. in Pakistani sheep - Wajiha Shahzadi; Mughees Akbar; Arooj Ijaz; Arshad Hussain; Umair Shabbir; Ioannis A. Giantsis; Shakir Ullah; Maged A. AlGaradi; Adil Khan; Furhan Iqbal; Ayman A. Swelum (PLoS ONE, 2025)
Pakistan has a huge sheep population (37.2 million in 2024) that is largely unexplored for the presence of vector transmitted parasites. Present study was aimed to document the prevalence of Anaplasma sp., Anaplasma ovis, Theileria ovis and Theileria lestoquardi in sheep blood samples (N = 329) that were collected from six districts (Muzaffargarh, Rajanpur, Dera Ghazi Khan, Layyah, Taunsa and Khanewal) during August till December 2024 and to report the genetic diversity of screened pathogens. Molecular analyses revealed that the prevalence of Anaplasma sp., Anaplasma ovis and Theileria ovis in screened sheep was 11%, 20% and 21% respectively. None of the screened sheep was Theileria lestoquardi infected. Co-infection of the screened pathogens was also observed. Presence of the detected pathogens was confirmed by DNA sequencing and subsequent BLAST analysis. Phylogenetic analysis revealed that these pathogens displayed genetic similarities with the sequences that were deposited from various countries across the globe. Prevalence of all screened pathogens varied significantly between the sampling districts. Similarly, the Anaplasma sp., Anaplasma ovis and Theileria ovis prevalence varied significantly among the sheep breeds. Anaplasma ovis infection was more common in large herds and in un-infested sheep. Theileria ovis infection was more frequent in small herds. In conclusion, we are reporting the presence of Anaplasma sp., Anaplasma ovis and Theileria ovis in Pakistani sheep that were enrolled from all six districts. Large-scale studies are recommended in various geo-climatic regions of Pakistan to confirm the genetic diversity, epidemiology and host-pathogen interactions that will contribute towards effective control of these infections among the local sheep population.